A stone is projected from a point on the ground in such a direction as to hit a bird on the top of a telegraph post of height
H
and then attain maximum height of
2
H
above the ground. If at the instant of projection, the bird were to fly away horizontally with uniform speed, Find the ratio between the horizontal velocity of bird and the stone, if the stone still hits the bird while descending.
The answer is of the form
b
c
+
d
a
.
Then enter the answer as
a
+
b
+
c
+
d
, where
a
,
b
,
c
,
d
are integers.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
can you please explain why v^2=(2H)(2g).
Derive using equations of motion.
conservation of energy (KE=PE at 2H)
Great solution.Did with a different but very lengthy way..Yours is better.
There is a slip! Distance is not the same . Time is the same. Distances are proportional to Velocity of stone. Can refer to my solution.
Could you explain why Vb t1 not Vb t2 ?
t 1 is the time at the the stone is at a height H while coming down.
I loved every bit of detail about this answer, thanks for putting in the time to do it !
why did you assume that the bird and the stone cover the same distance? they are not at the same starting point, or are they?
They are not at the same starting point. Think again, the condition for collision is pretty simple.
Staring points are not the same. Only the time is same. Refer to my solution.
This problem deals with a parabola and it's generic. Speeds are proportional to distances
Imgur
This is a parabola with equation
y
=
x
2
. Now, Co-ordinates of the point shown are
(
−
1
,
1
)
,
(
1
,
1
)
a
n
d
(
2
,
2
)
. Thus the required ratio is
1
+
2
2
.
Hence the answer
6
Imgur
Let the time for the STONE to rise from ground to 2 H and fall from 2 H to ground each be equal to T .
L
e
t
t
h
e
t
i
m
e
f
o
r
t
h
e
S
T
O
N
E
t
o
r
i
s
e
f
r
o
m
H
t
o
2
H
a
n
d
f
a
l
l
f
r
o
m
2
H
t
o
H
e
a
c
h
b
e
e
q
u
a
l
t
o
t
.
T
o
t
a
l
h
o
r
i
z
o
n
t
a
l
d
i
s
t
a
n
c
e
a
n
d
v
e
l
o
c
i
t
y
o
f
t
h
e
b
i
r
d
a
r
e
s
a
y
D
B
a
n
d
V
B
;
a
n
d
t
h
o
s
e
o
f
t
h
e
s
t
o
n
e
,
D
S
a
n
d
V
S
.
H
=
(
1
/
2
)
g
t
2
a
n
d
2
H
=
(
1
/
2
)
g
T
2
.
∴
T
=
2
∗
t
.
~~~\color \red{The~ time~ taken~ by~each~ is~ the~ same}=Total~ time =TT.
∴
T
T
=
T
+
t
=
2
∗
t
+
t
=
(
1
+
2
)
∗
t
E
q
u
a
l
T
i
m
e
M
E
T
H
O
D
:
−
D
B
=
V
S
∗
(
t
+
t
)
,
D
S
=
V
S
∗
T
T
\displaystyle \therefore \dfrac{V_B}{V_S}= \dfrac {D_B/TT}{D_S/TT}=\dfrac{V_S * (2t)}{V_S*TT}= \frac{2t}{(1*\sqrt2+1)*t}~~=\frac{a}{b * \sqrt c+d}. \\a+b+c+d= 2+1+2+1=\boxed{6}\\\\~~\\~~\\OR\\ \\\color \red{Equal~Distance~METHOD:-} \\The~bird~covers~D_B~with~V_B~in~Time~TT=(1+\sqrt2)*t. \\Same~distance~is~covered~by~the~stone~~with~V_S~~in~2t.\\ \displaystyle \therefore~V_B*(\sqrt2+1)*t=V_S*2*t...\displaystyle {.....\frac{V_B }{V_S }=\frac{2t }{(1*\sqrt2+1)*t}=\frac{a}{b*\sqrt c+d } }\\a+b+c+d =2+1+2+1 =6.\\\boxed{6}
We know that a projectile is a parabola. Consider the topmost point as the origin (O). Let bird be at A initially and let projectile be fired from P. Along Y-axis, OA is equal to H and OP is 2H.
By nature of parabola, along X-axis if OA is taken as 1 (say) then OP will be sqrt(2). As time required by bullet and bird is same, speeds are proportional to distance.
Horizontal distance by bird = 1 + 1 = 2 Horizontal distance by bullet = sqrt(2) + 1 which gives us a=2, b=1, c=2, d=1 and answer = 6.
nice approach .! well this is a straight question from DC Pandey Mechanics Subjective problems
Yep..i was laughing wen i saw it
Problem Loading...
Note Loading...
Set Loading...
Let horizontal velocity of stone be v x , vertical velocity be v y and velocity of bird be v b .
Since the maximum height of the stone is 2 H ,
( v y ) 2 = ( 2 H ) ( 2 g )
Now, Writing equation of motion for the vertical,
H = v y t − 2 1 g t 2
Let t 1 and t 2 be the times at which the stone achieves the height H. Then, t 1 and t 2 are the roots of the above equation, with t 1 > t 2
t 1 = g v y + ( v y ) 2 − 2 H g a n d t 2 = g v y − ( v y ) 2 − 2 H g
Substitute value of v y here.
We get,
t 1 = g 2 H g + 2 H g a n d t 2 = g 2 H g − 2 H g
t 1 − t 2 = 2 g 2 H g
NOTE that if the stone is to hit the bird, then they must cover same distances.
v x ( t 1 − t 2 ) = v b t 1
Substituting,
2 v x 2 H g = v b ( 2 H g + 2 H g )
v x v b = 2 + 1 2
Thus, a + b + c + d = 6